A review of cetacean research and conservation in Sri Lanka - Ilangakoon, Anoukchika D. (J. Cetacean Res. Manage., 2023)
Sri Lanka is a developing island nation in the northern Indian Ocean. Travellers and historians have documented whales in the waters around the island as far back as the 14th century but the first scientific records of live cetaceans from vessel-based research observations were documented only in the early 1980s. Sri Lanka’s waters have high cetacean species richness with 27 species recorded to date and year-round abundance. Small cetaceans are however increasingly threatened due to the developing fisheries industry, with bycatch being a major cause for concern. Other identified threats include increasing shipping traffic and unregulated marine tourism. Cetaceans are protected by national legislation but implementation of the relevant laws and conservation measures is hampered by resource constraints. The prevailing gaps in knowledge are also due to a lack of resources to carry out dedicated long-term research on cetaceans in a developing country with more immediate human development priorities. Therefore strengthened law enforcement and finding adequate resources for sustained systematic research that can inform management decisions are priorities in Sri Lanka.